Analisis Penerapan Manajemen Risiko Terhadap Kualitas Produktivitas Agen BRILink Sebagai Pendorong Financial Inclusion: Studi Kasus: PT Bank Rakyat Indonesia Regional Office Malang - Wildan Dzulfaqor; Abdul Moin (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This research focuses on a company engaged in the banking sector, namely BRI. The company has a service called BRILink, a system created to make it easier for customers. This study aims to apply risk management theory to encourage corporate financial inclusion. This research uses descriptive qualitative research methods by conducting observations, interviews, and documentation in Malang. Researchers find potential in applying risk management theory to the quality of agent productivity. Researchers hope that companies can improve their services by implementing risk management.